Identification of Drug Material Melting Conditions from Hot-Stage Microscopy Images Using Active Contour and Support Vector Machine Methods - Reski, Julia Mega; Ramadhani, Muhammad (Indonesian Scientific Journal, 2026)
The hospital pharmacy installation plays an essential role in ensuring the quality of pharmaceutical supplies. One important stage in drug production is raw material analysis, particularly melting point determination as a purity indicator. Conventional methods, such as capillary tubes, are limited in accuracy and prone to subjectivity. This study aims to develop an automated image-based monitoring system integrated with Hot Stage Microscopy (HSM) to objectively detect real-time morphological changes in pharmaceutical materials. The system was designed using digital image processing stages consisting of image acquisition, processing, and output. Images were captured using a binocular microscope and processed on an Odroid XU4 mini-computer. Phase boundaries were identified using the Active Contour segmentation method, while texture features were extracted using the Gray Level Co-occurrence Matrix (GLCM) at four orientation angles. Classification was performed using a Support Vector Machine (SVM) with a Radial Basis Function (RBF) kernel. The results showed that the Active Contour method effectively detected melting phases, and the SVM achieved an accuracy of 91.67%, precision of 91.89%, sensitivity of 91.67%, and an F1-score of 91.66%. The system successfully distinguished pure Paracetamol from mixtures with Gallic Acid and Ferulic Acid.